Physical chemistry in a single live cell: confocal microscopy. Issue 20 (10th May 2017) - Amin, Md. Asif; Nandi, Somen; Mondal, Prasenjit; Mahata, Tanushree; Ghosh, Surajit; Bhattacharyya, Kankan
Abstract : A confocal microscope can be used to differentiate between cancer and non-cancer cells, and to enrich our knowledge of 3D tumor spheroids and drug delivery. Abstract : A live cell is a complex, yet extremely important container. Understanding the dynamics in a selected intracellular component is a challenging task. We have recently made significant progress in this direction using a confocal microscope as a tool. The smallest size of the focused spot in a confocal microscope is ∼0.2 μm (200 nm). This is nearly one hundred times smaller than the size of a live cell. Thus, one can selectively study different intracellular components/organelles in a live cell. In this paper, we discuss how one can image different intracellular components/organelles, record fluorescence spectra and decay at different locations, ascertain local polarity and viscosity, and monitor the dynamics of solvation, proton transfer, red-ox and other phenomena at specified locations/organelles inside a cell. We will highlight how this knowledge enriched us in differentiating between cancer and non-cancer cells, 3D tumor spheroids and towards drug delivery.